Fontes do crescimento econômico no Nordeste: uma avaliação do período entre 2004 e 2013 - SOUSA, Roseane Moura (2016)
Evidence about the economic growth in the Northeast in the period between 2004 and 2013. Search the thinkers of the regional issue in the Northeast the theorical framework for solution of inequalities. Analyzes the degree of regional inequality in various aspects and draws a comparison of the Region states among themselves and with other regions of the country, with the foundation theories of growth and economic development. Using the methodology used in the empirical literature is intended to analyze the indicators that attest to the region's growth. Investigates possible changes in the economic structure and the mains determinants of the variations of the product states that make up that region. In this direction, the results were presented at the end of the study indicate that the improvement in the levels of employment and income in the region goes through initiatives that focus on the increase in total productivity of production factors. It is expected that over the next few years the trend here checked prevail, so that the North undergoes a transformation that generates higher levels of employment, income and comprehensively, increase their standard of development.